2015
DOI: 10.7708/ijtte.2015.5(4).06
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Bus Travel Time Using Artificial Neural Network

Abstract: The objective of this study is to apply artificial neural network (ANN) for development of bus travel time prediction model. The bus travel time prediction model was developed to give real time bus arrival information to the passenger and transit agencies for applying proactive strategies. For development of ANN model, dwell time, delays and distance between the bus stops was taken as input data. Arrivals/departure times, delays, average speed between the bus stop and distance between the bus stops were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…Many interesting neural network projects have been carried out ever since its introduction, for instance, the famous DeepMind by Google to play board games against professionals has gained huge success from it. ANN consists of a few layers, generally the input layer, hidden layer (there can be multiple hidden layers depending on the complexity of the problem) and output layer [22]. All the layers are interconnected, where the input layer consists of all the input variables, and all the input layers are connected to the hidden layers, and the hidden layer is connected to the output layer.…”
Section: Machine Learning Modelmentioning
confidence: 99%
“…Many interesting neural network projects have been carried out ever since its introduction, for instance, the famous DeepMind by Google to play board games against professionals has gained huge success from it. ANN consists of a few layers, generally the input layer, hidden layer (there can be multiple hidden layers depending on the complexity of the problem) and output layer [22]. All the layers are interconnected, where the input layer consists of all the input variables, and all the input layers are connected to the hidden layers, and the hidden layer is connected to the output layer.…”
Section: Machine Learning Modelmentioning
confidence: 99%
“…Results indicated that the model performed well in terms of reducing relative mean errors and root-mean-squared errors in relation to other models. Amita et al (2015) employed Artificial Neural Network to develop a bus travel time prediction model and when the model used to predict bus travel time underperformed compared with other models in terms of accuracy and robustness. In general, factors that influence urban travel time are intercorrelated with each other, which limits the applicability of the regression models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Artificial Neural Network (ANN) models have been developed to complement the weakness found in the regression model. Many researchers have opted to use the model to predict urban travel time because of their ability to solve complicated nonlinear relationships in traffic f low prediction (Amita et al, 2015;Bai et al, 2015;Fan and Gurmu, 2015;Chien et al, 2002). Zheng and Van Zuylen (2013) applied an Artificial Neural Network (ANN) model to estimate urban link travel time using speed, position and time-stamped from the probe vehicle as input data.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A link based ANN model for travel time prediction was proposed using a feed-forward network for training the network and logistic sigmoid function as activation function (Nahar and Sultana, 2014). A bus travel time prediction model was developed using Artificial Neural Network (ANN) model by taking dwell time, delays and distance between the bus stops as inputs (Amita et al, 2015). Model was developed, validated and tested using GPS (Global Positioning System) data collected from field study.…”
Section: Reviewmentioning
confidence: 99%